2021
DOI: 10.1080/09712119.2021.1926258
|View full text |Cite
|
Sign up to set email alerts
|

Oregano-oil antagonist lipopolysaccharide (LPS) induced toxicity in pre- and post-hatch chick embryo

Abstract: Oregano essential oil (OEO), one kind of Labiata has been known for a long time as a popular remedy. The essential oil of oregano has anti-bacterial, anti-oxidant, anti-fungal and nematicidal properties mainly due to the basic constituents. Once the shell's microbial barriers have been breached, Gram-negative bacteria are more capable of withstanding the antimicrobials present in the albumen. Eggs were divided into, control group (GI), LPS group (GII) and LPS plus OEO 0.5% group (GIII), as natural disinfectant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…No harmful effects on organ development during embryogenesis and post-hatch were reported in eggs sanitized with clove essential oil [ 10 ]. Bekhet and Sayed [ 82 ] observed that treating eggs with essential oregano oil did not cause malformations in embryos, benefiting them by restoring their antioxidant balance. Gholami-Ahangaran et al [ 3 ], Batkowska et al [ 43 ] and Oliveira et al [ 10 ] reported improvement in the survival percentage of chicks from eggs sanitized with Virkon S, propolis and clove essential oil, respectively, in the first days of post-hatch life.…”
Section: Sanitizers and Their Effects On The Microbiological Quality ...mentioning
confidence: 99%
“…No harmful effects on organ development during embryogenesis and post-hatch were reported in eggs sanitized with clove essential oil [ 10 ]. Bekhet and Sayed [ 82 ] observed that treating eggs with essential oregano oil did not cause malformations in embryos, benefiting them by restoring their antioxidant balance. Gholami-Ahangaran et al [ 3 ], Batkowska et al [ 43 ] and Oliveira et al [ 10 ] reported improvement in the survival percentage of chicks from eggs sanitized with Virkon S, propolis and clove essential oil, respectively, in the first days of post-hatch life.…”
Section: Sanitizers and Their Effects On The Microbiological Quality ...mentioning
confidence: 99%